Issues in the Assessment of the Exchange Rates of Industrial Countries. (Occasional Papers; Occasional Paper, 1984)
In its surveillance activities, the Fund is frequently confronted with the difficult problem of how to identify exchange rate behavior that is unrelated to underlying economic and financial conditions and, consequently, should be viewed with concern from a national or international standpoint. This paper considers the various issues related to this problem as it pertains to industrial countries, both those that have independently floating exchange rates and those that operate under other exchange arrangements.